IMPAC OF VOLATILITY EXCHANGE RATES ON INDONESIAN ELECTRONIC IMPORTS FROM INTRA AND EXTRA ASEAN - Imam Muklis (Economic Journal of Emerging Markets, 2010)
This study analyzes the effects of exchange rates volatility and Gross Domestic Product (GDP) onelectronic commodity import demand in Indonesia from intra and extra ASEAN. It applies an ErrorCorrection Model along with Dickey-Fuller and Augmented Dickey-Fuller tests. It finds that Indonesianimport demand for electronic commodity is significantly affected by GDP only in the shortrun. It also finds that exchange rates volatility in the short run have a negative effect on import demandfrom intra ASEAN and have a positive effect from extra ASEAN. In the long term, Indonesianimport demand from extra ASEAN is positively affected only by exchange rates volatility.Keywords: Exchange rates volatility, error correction model, gross domestic product, ASEANJEL classification numbers: F14, F31